Components of genetic associations across 2,138 phenotypes in the UK Biobank highlight adipocyte biology - Yosuke Tanigawa (Nature Portfolio, 2019)
While many pleiotropic genetic loci have been identified, how they contribute to phenotypes across traits and diseases is unclear. Here, the authors propose decomposition of genetic associations (DeGAs), which uses singular value decomposition, to characterize the underlying latent structure of genetic associations of 2,138 phenotypes.